Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/es501757s
|View full text |Cite
|
Sign up to set email alerts
|

Large Accumulation of Micro-sized Synthetic Polymer Particles in the Sea Surface Microlayer

Abstract: Determining the exact abundance of microplastics on the sea surface can be susceptible to the sampling method used. The sea surface microlayer (SML) can accumulate light plastic particles, but this has not yet been sampled. The abundance of microplastics in the SML was evaluated off the southern coast of Korea. The SML sampling method was then compared to bulk surface water filtering, a hand net (50 μm mesh), and a Manta trawl net (330 μm mesh). The mean abundances were in the order of SML water > hand net > b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
215
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 480 publications
(236 citation statements)
references
References 34 publications
(63 reference statements)
12
215
1
8
Order By: Relevance
“…Their presence in surface water (Barnes et al 2009;Song et al 2014), beaches and sediment (Katsanevakis et al 2007) has been reported from many parts of the world, including even the Arctic (Obbard et al 2014). Additionally, microplastics have been reported in estuaries and freshwater bodies (Lima et al 2014).…”
Section: Microplastics In the Oceansmentioning
confidence: 99%
“…Their presence in surface water (Barnes et al 2009;Song et al 2014), beaches and sediment (Katsanevakis et al 2007) has been reported from many parts of the world, including even the Arctic (Obbard et al 2014). Additionally, microplastics have been reported in estuaries and freshwater bodies (Lima et al 2014).…”
Section: Microplastics In the Oceansmentioning
confidence: 99%
“…The North Pacific Ocean and its marginal seas have the highest microplastic contamination levels in the world (Eriksen et al 2014;Song et al 2014;Cózar et al 2015). Therefore, it is important to collect and share information on microplastic pollution in the North Pacific region among global scientific and policy audiences.…”
Section: Papers Presented In This Special Issuementioning
confidence: 99%
“…One estimate for the minimum total quantity of floating plastic litter ([0.33 mm in size) in the oceans is 0.27 tons (5.25 trillion particles), with microplastics (0.33-4.75 mm in size) accounting for 92 % by number of plastic particles and 13 % by weight (Eriksen et al 2014). However, these data do not include plastics on the seabed (Woodall et al 2014) and beaches (Browne et al 2010) or those of particle size 0.001-0.33 mm, which account for the majority of the total abundance of microplastics (Song et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This could be relevant to the study of the biodegradation of oil products forming oil slicks at the sea surface [45], and associated impacts on marine biota and ecosystem functioning [46]. Another application for the SISI might be the incubation of water samples containing microplastics, whose higher abundance in the SML, compared to underlying water, has been recently described [47]. Bacterial colonization of polymer-based materials and biofilm formation [48], as well as microbial degradation of microplastic particles [49], constitute highly topical research areas that could be further investigated using the SISI.…”
Section: Future Research Directionsmentioning
confidence: 99%